2015
DOI: 10.21668/health.risk/2015.2.09.eng
|View full text |Cite
|
Sign up to set email alerts
|

Toxicological evaluation of nano-sized colloidal silver in experiments on mice. behavioral reactions, morphology of internals

Abstract: The results of toxicity studies of nano-sized colloidal silver (NCC), the most widely used in medicine, food and life, are given. When evaluating safe doses of silver NP (using commercially available NCC solution stabilized with polyvinylpyrrolidone (PVP), with the size of silver NP at the range of 5-80 nm) when orally administered to male mice, BALB/c mice at doses of 0.1; 1.0 and 10 mg/kg of body weight per silver different effects from the motor and orienting-exploratory activity were revealed, for the part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Various dose-dependent effects on behavioral reactions were revealed in male BALB/c mice with Open field Animal test; these effects included a decrease in frequency of actions that required physical efforts and shorter periods of time spent on such actions; greater anxiety as per parameters of frequency and duration of orientation and exploration activities and grooming. Morphological research revealed changes in liver and spleen tissues, and, to a smaller extent, heart and kidneys tissues; a range of these changes and their intensity grew together with an increase in NMs doses [29]. A similar experiment performed on male Wistar rats allowed to reveal adverse shifts under exposure to a NM dose equal to 10 mg/kg of body weight recalculated per Ag as per parameters of body weight growth, relative lungs weight, average volume of an erythrocyte, hemoglobin concentration in erythrocytes, and relative fraction of neutrophils and lymphocytes.…”
Section: Scientific Research Institute Of Nutrition and Rospotrebnadzmentioning
confidence: 99%
“…Various dose-dependent effects on behavioral reactions were revealed in male BALB/c mice with Open field Animal test; these effects included a decrease in frequency of actions that required physical efforts and shorter periods of time spent on such actions; greater anxiety as per parameters of frequency and duration of orientation and exploration activities and grooming. Morphological research revealed changes in liver and spleen tissues, and, to a smaller extent, heart and kidneys tissues; a range of these changes and their intensity grew together with an increase in NMs doses [29]. A similar experiment performed on male Wistar rats allowed to reveal adverse shifts under exposure to a NM dose equal to 10 mg/kg of body weight recalculated per Ag as per parameters of body weight growth, relative lungs weight, average volume of an erythrocyte, hemoglobin concentration in erythrocytes, and relative fraction of neutrophils and lymphocytes.…”
Section: Scientific Research Institute Of Nutrition and Rospotrebnadzmentioning
confidence: 99%